NaYF4:Er3+,Yb3+/SiO2 Core/Shell Upconverting Nanocrystals for Luminescence Thermometry up to 900 K - Geitenbeek, Robin G; Prins, P Tim; Albrecht, Wiebke; van Blaaderen, Alfons; Weckhuysen, Bert M; Meijerink, Andries (Journal of physical chemistry. C, 2017)
The rapid development of nanomaterials with unique size-tunable properties forms the basis for a variety of new applications, including temperature sensing. Luminescent nanoparticles (NPs) have demonstrated potential as sensitive nanothermometers, especially in biological systems. Their small size offers the possibility of mapping temperature profiles with high spatial resolution. The temperature range is however limited, which prevents use in high-temperature applications such as, for example, nanoelectronics, thermal barrier coatings, and chemical reactors. In this work, we extend the temperature range for nanothermometry beyond 900 K using silica-coated NaYF4 nanoparticles doped with the lanthanide ions Yb3+ and Er3+. Monodisperse ∼20 nm NaYF4:Yb,Er nanocrystals were coated with a ∼10 nm silica shell. Upon excitation with infrared radiation, bright green upconversion (UC) emission is observed. From the intensity ratio between 2H11/2 and 4S3/2 UC emission lines at 520 and 550 nm, respectively, the temperature can be determined up to at least 900 K with an accuracy of 1-5 K for silica-coated NPs. For bare NaYF4:Yb,Er NPs, the particles degrade above 600 K. Repeated thermal cycling experiments demonstrate the high durability and reproducibility of the silica-coated nanocrystals as temperature probes without any loss of performance. The present results open avenues for the development of a new class of highly stable nanoprobes by applying a silica coating around a wide variety of lanthanide-doped NPs.